A curve tracing algorithm using level set based affine transforms - Lam, B.S.Y.; Van, H. (2005 IEEE International Conference on Systems, Man and Cybernetics, 2005)
Existing curve tracing algorithms drive an evolving curve to the mean or median of the data. However, if the data set contains heavy noise, these algorithms may not produce correct results. In this paper, we introduce a level set based affine transform method to enhance the capability of a class of fuzzy curve tracing algorithms. The essential idea of our approach is to drive the initial curve towards the object data using level sets as well as affine transforms. Experimental results show that the proposed method can enhance fuzzy curve tracing algorithms for dealing with the data corrupted by noise.